2018
DOI: 10.3389/fpsyt.2018.00279
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Cognitive Function in Patients With Schizophrenia and Bipolar Disorder, and Healthy Controls

Abstract: Background: This study compared adaptive resilience among patients with schizophrenia, bipolar disorder, and healthy controls, and examined the relationship of resilience to cognitive function.Methods: A sample of 81 patients diagnosed with schizophrenia, 34 with bipolar disorder, and 52 healthy controls completed the Connor-Davidson Resilience Scale (CD-RISC) and cognitive tests of verbal comprehension, executive functioning, and working memory. Paired comparison of diagnostic groups on CD-RISC and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 36 publications
3
20
2
Order By: Relevance
“…The social-cognitive bias score was higher in the UHR group than in the other two groups, yet not significantly so. This finding is not compatible with previous findings of bias in UHR (40, 73) and first-episode groups (73). However, it may be derived from the differences of hostility perception and blaming bias scoring; the AIHQ scoring in the previous study was related to the ambiguous situations, and not to the intentional and accidental ones.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The social-cognitive bias score was higher in the UHR group than in the other two groups, yet not significantly so. This finding is not compatible with previous findings of bias in UHR (40, 73) and first-episode groups (73). However, it may be derived from the differences of hostility perception and blaming bias scoring; the AIHQ scoring in the previous study was related to the ambiguous situations, and not to the intentional and accidental ones.…”
Section: Discussioncontrasting
confidence: 99%
“…Since higher reflective self factor score implies lower self-esteem and resilience and higher anhedonia, the score of the HC group was the lowest of the three groups, as expected. This finding was compatible with previous reports of lower resilience and self-esteem in patient groups (38, 73). The UHR group showed higher reflective self score than the ROSPR group.…”
Section: Discussionsupporting
confidence: 93%
“…Dosages of antipsychotics in all patients were converted to chlorpromazine equivalence (28). In addition, all participants completed the Information (WAIS-I) and Digit Symbol (WAIS-DS) subtests of the Wechsler Adult Intelligence Scale (29), which measure two important domains of cognitive functions, verbal comprehension and processing speed, respectively (30,31).…”
Section: Subjects and Measurementsmentioning
confidence: 99%
“…A previous study revealed that resilience negatively correlated with negative indicators of mental health and positively did with positive indicators of it 1. Furthermore, a previous study described that schizophrenia and bipolar disorder patients showed a lower level of resilience than healthy people 7. As for eating disorders, it was reported that resilience predicted improvement in psychological health and social relationship domains of quality of life and reduction of eating disorder symptoms over time 8…”
Section: Introductionmentioning
confidence: 99%